Catalyst body for reverse water gas shift reaction
By using a catalyst containing d-zone elements and Group 13 or Group 14 elements in the reverse-hydraulic gas shift reaction, combined with oxides as support, the problem of methane by-products when CO2 is converted to CO is solved, and high CO selectivity and reaction efficiency are improved.
Patent Information
- Application Number
- JP2023167863
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-09
AI Technical Summary
In the reverse-hydraulic gas shift reaction, when CO2 is efficiently converted to CO, it is easy to generate stable and difficult to reuse methane (CH4) by-products, resulting in a decrease in CO selectivity.
A catalyst containing d-region elements (such as Co, Fe, Cu) and Group 13 or Group 14 elements (such as In, Ge, Sn) is used, and combined with oxides (such as CeO2) as support, improve the CO selectivity of the catalyst and inhibit the formation of methane.
Through this catalyst structure, the selectivity of CO can be significantly improved, the formation of methane can be reduced, and the efficiency of the reverse-hydraulic gas shift reaction can be improved.
Smart Images

Figure 2025057982000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a catalyst for a reverse water gas shift reaction. [Background technology]
[0002] In recent years, efforts to realize a carbon-free society have been gaining momentum, and chemical synthesis using carbon dioxide (CO2) as a raw material has attracted attention. To achieve this, the resource recovery process through the hydrogenation reaction of CO2 is important. In particular, the conversion of CO2 to carbon monoxide (CO), which is used as a raw material in various chemical synthesis processes, is considered important. The reaction (CO2+H2→CO+H2O) to produce CO from CO2 and hydrogen (H2) is called the reverse water-gas shift reaction. However, since it is not easy to convert chemically stable CO2 into CO, catalysts such as cobalt (Co) are used to promote the reverse water-gas shift reaction.
[0003] In addition, the prior non-patent document 1 describes the use of CeO2 for catalytic reduction of CO2 to CO by the reverse water gas shift reaction. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] MinZhu, Qingfeng Ge, Xinli Zhu “Catalytic Reduction of CO2 to CO via Reverse Water Gas Shift Reaction : Recent Advances in the Design of Active and Selective Supported Metal Catalysts” (2020) Summary of the Invention [Problem to be solved by the invention]
[0005] In the reverse water gas shift reaction, it is important to efficiently convert CO2 to CO. However, in reality, methane (CH4) is produced as a by-product. CH4 is a very stable substance, so once it is produced, it is extremely difficult to reuse it as a raw material in the process. Therefore, it is important to develop a catalyst that produces only CO with high selectivity without producing CH4. Co, which has been used as a catalyst until now, can activate CO2 at relatively low temperatures and has a high CO2 conversion rate, but has the problem that a large amount of CH4 is produced even at relatively low temperatures due to its high hydrogenation activity.
[0006] The present invention has been made in view of the above background, and aims to provide a catalyst for reverse water gas shift reaction that can suppress the production of CH4 and improve CO selectivity. [Means for solving the problem]
[0007] One aspect of the present invention is The catalyst has an oxide capable of adsorbing carbon dioxide gas on its surface, and a catalyst; The catalyst comprises a main element consisting of a d-block element and a sub-element consisting of at least one of a Group 13 element and a Group 14 element, A catalyst for the reverse water gas shift reaction. Effect of the Invention
[0008] The catalyst body for the reverse water gas shift reaction has the above-mentioned configuration, and therefore, the catalyst body for the reverse water gas shift reaction can suppress the production of CH4 and improve the CO selectivity. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a graph showing the relationship between temperature (°C) (horizontal axis) and CO conversion (%) (vertical axis) for each of the catalysts Co(20) / CeO2, Fe(20) / CeO2, and Cu(20) / CeO2 obtained in Experimental Example 1. [Diagram 2] FIG. 2 is a graph showing the relationship between temperature (°C) (horizontal axis) and CO selectivity (%) for each of the catalysts Co(20) / CeO2, Fe(20) / CeO2, and Cu(20) / CeO2 obtained in Experimental Example 1. [Diagram 3] FIG. 3 is a graph showing the relationship between temperature (°C) (horizontal axis) and CO conversion (%) (vertical axis) for each of the catalysts Co(20) / CeO2, Co(20)-Ge(2) / CeO2, Co(20)-Sn(2) / CeO2, and Co(20)-In(2) / CeO2 obtained in Experimental Example 2. [Figure 4] FIG. 4 is a graph showing the relationship between temperature (°C) (horizontal axis) and CO selectivity (%) (vertical axis) for each of the catalysts Co(20) / CeO2, Co(20)-Ge(2) / CeO2, Co(20)-Sn(2) / CeO2, and Co(20)-In(2) / CeO2 obtained in Experimental Example 2. [Diagram 5] FIG. 5 shows X-ray diffraction patterns (XRD patterns) obtained in Experimental Example 2 for the catalysts Co(20) / CeO2, Co(20)-Ge(2) / CeO2, Co(20)-Sn(2) / CeO2, and Co(20)-In(2) / CeO2 before reduction treatment (immediately after calcination). [Figure 6] FIG. 6 shows the results of temperature-programmed reduction measurements (H2-TPR) obtained in Experimental Example 2 for the Co(20) / CeO2, Co(20)-Ge(2) / CeO2, Co(20)-Sn(2) / CeO2, and Co(20)-In(2) / CeO2 catalysts before reduction treatment (immediately after calcination). [Figure 7]FIG. 7 shows X-ray diffraction patterns (XRD patterns) for the catalysts Co(20) / CeO2, Co(20)-Ge(2) / CeO2, Co(20)-Sn(2) / CeO2, and Co(20)-In(2) / CeO2 after reduction treatment, obtained in Experimental Example 2. [Figure 8] FIG. 8 is a graph showing the relationship between temperature (°C) (horizontal axis) and CO2 conversion (%) (vertical axis) for each Co-Ge / CeO2 catalyst having a different Ge loading, obtained in Experimental Example 3. [Figure 9] FIG. 9 is a diagram showing the relationship between temperature (°C) (horizontal axis) and CO selectivity (%) for each Co-Ge / CeO2 catalyst having a different Ge loading amount, obtained in Experimental Example 3. [Figure 10] FIG. 10 is a graph showing the relationship between CO conversion (%) (horizontal axis) and CO selectivity (%) for each Co-Ge / CeO catalyst having a different Ge loading amount, obtained in Experimental Example 3. [Figure 11] FIG. 11 is a diagram showing X-ray diffraction patterns (XRD patterns) for each of the Co-Ge / CeO2 catalyst bodies having different amounts of Ge supported thereon before reduction treatment (immediately after calcination) obtained in Experimental Example 3. [Figure 12] FIG. 12 is a diagram showing the results of temperature-programmed reduction measurements (H2-TPR) obtained in Experimental Example 3 for each Co-Ge / CeO2 catalyst having a different amount of Ge loaded thereon before reduction treatment (immediately after calcination). [Figure 13] FIG. 13 is a diagram showing X-ray diffraction patterns (XRD patterns) for each of the Co-Ge / CeO2 catalyst bodies having different amounts of Ge supported thereon after reduction treatment, obtained in Experimental Example 3. [Figure 14]FIG. 14 is a diagram showing X-ray diffraction patterns (XRD patterns) for each of the Co-Ge / CeO2 catalyst bodies having different amounts of Ge supported thereon after the reverse water gas shift reaction experiment, obtained in Experimental Example 3. [Figure 15] FIG. 15 is a diagram showing the results of STEM-EDS analysis of the Co(20) / CeO2 catalyst body after reduction treatment, obtained in Experimental Example 4. [Figure 16] FIG. 16 is a diagram showing the results of STEM-EDS analysis (at a higher magnification than FIG. 15) of the Co(20) / CeO2 catalyst body after reduction treatment, obtained in Experimental Example 4. [Figure 17] FIG. 17 is a diagram showing the results of STEM-EDS analysis of the Co(20)-Ge(20) / CeO2 catalyst body after reduction treatment, obtained in Experimental Example 4. [Figure 18] FIG. 18 is a diagram showing the results of STEM-EDS analysis (at a higher magnification than FIG. 18) of the Co(20)-Ge(20) / CeO2 catalyst body after reduction treatment, obtained in Experimental Example 4. [Figure 19] FIG. 19 shows the results of STEM-EDS analysis of the Co(20)-Ge(20) / CeO2 catalyst body before reduction treatment (immediately after calcination) and after the reverse water gas shift reaction, obtained in Experimental Example 4. [Figure 20] FIG. 20 is a graph showing the relationship between temperature (°C) (horizontal axis) and CO conversion (%) (vertical axis) for each of the catalysts Fe(20) / CeO2, Cu(20) / CeO2, and Co(20)-Ge(10) / CeO2 obtained in Experimental Example 5. [Figure 21] FIG. 21 is a graph showing the relationship between temperature (°C) (horizontal axis) and CO selectivity (%) for each of the catalysts, Fe(20) / CeO2, Cu(20) / CeO2, and Co(20)-Ge(10) / CeO2, obtained in Experimental Example 5. [Figure 22]FIG. 22 is a graph showing the relationship between temperature (°C) (horizontal axis) and CO conversion (%) (vertical axis) for each Co-In / CeO catalyst having a different amount of In supported, obtained in Experimental Example 6. [Figure 23] FIG. 23 is a diagram showing the relationship between temperature (°C) (horizontal axis) and CO selectivity (%) for each of the Co-In / CeO2 catalysts having different amounts of In carried, obtained in Experimental Example 6. [Figure 24] FIG. 24 is a diagram showing X-ray diffraction patterns (XRD patterns) obtained in Experimental Example 6 for each of the Co-In / CeO2 catalyst bodies having different amounts of In supported thereon before reduction treatment (immediately after calcination). [Diagram 25] FIG. 25 is a diagram showing the results of temperature-programmed reduction measurements (H2-TPR) obtained in Experimental Example 6 for each of the Co-In / CeO2 catalyst bodies having different amounts of In loaded thereon before reduction treatment (immediately after calcination). [Figure 26] FIG. 26 is a diagram showing X-ray diffraction patterns (XRD patterns) for each of the Co-In / CeO2 catalyst bodies having different amounts of In supported thereon after reduction treatment, obtained in Experimental Example 6. [Figure 27] FIG. 27 is a diagram showing the relationship between temperature (°C) (horizontal axis) and CO yield (%) (vertical axis) for each of the catalysts Co(20) / CeO2, Fe(20) / CeO2, and Cu(20) / CeO2 obtained in Experimental Example 7. [Figure 28] FIG. 28 is a diagram showing the relationship between temperature (°C) (horizontal axis) and CO yield (%) (vertical axis) for each of the catalysts, Co(20) / CeO2, Co(20)-Ge(2) / CeO2, Co(20)-Sn(2) / CeO2, and Co(20)-In(2) / CeO2, obtained in Experimental Example 7. [Figure 29]FIG. 29 is a diagram showing the relationship between temperature (°C) (horizontal axis) and CO yield (%) (vertical axis) for each Co-Ge / CeO2 catalyst having a different Ge loading amount, obtained in Experimental Example 7. [Diagram 30] FIG. 30 is a diagram showing the relationship between temperature (°C) (horizontal axis) and CO yield (%) (vertical axis) for each of the catalysts, Fe(20) / CeO2, Cu(20) / CeO2, and Co(20)-Ge(10) / CeO2, obtained in Experimental Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the catalyst body for the reverse water gas shift reaction of the present disclosure will be described in detail using embodiments. Note that the catalyst body for the reverse water gas shift reaction of the present disclosure is not limited to the following examples of the embodiments.
[0011] The catalyst for reverse water gas shift reaction of this embodiment (hereinafter sometimes abbreviated as "the catalyst") is a catalyst used to promote the reverse water gas shift reaction (CO2+H2→CO+H2O). By using the catalyst for the reverse water gas shift reaction, it is possible to produce CO from a mixed gas containing, for example, CO2 and H2. The catalyst has an oxide and a catalyst.
[0012] In the present catalytic body, the oxide is capable of adsorbing carbon dioxide gas (CO2 gas) on its surface. The oxide may be capable of physically adsorbing CO2 gas on its surface, or may be capable of chemically adsorbing CO2 gas. The oxide is made to exist as something separate from the catalyst, and can have the function of supporting the catalyst. In other words, the present catalytic body can be said to have an oxide as a support and a catalyst supported on the oxide. However, the above-mentioned support includes a state in which the oxide and the catalyst are mixed (mixed), a state in which the catalyst is supported on the oxide surface, and a state in which the catalyst is taken into the oxide. The above-mentioned oxide may have a catalytic function of promoting the reverse water gas shift reaction, although it is separate from the catalyst. This is because the catalytic activity of the reverse water gas shift reaction is increased as a whole of the present catalytic body. In the present catalytic body, the catalyst is preferably supported on the oxide surface from the viewpoint of high activation due to an increase in the contact opportunity between the catalyst and CO2. In this case, the present catalytic body can specifically be configured such that a plurality of catalyst particles smaller than the oxide are supported on the oxide surface.
[0013] Examples of oxides include ceria (CeO2), ceria-based solid solutions, aluminum oxide (Al2O3), titanium oxide (TiO2), calcium oxide (CaO), zinc oxide (ZnO), etc. These can be used alone or in combination of two or more. Specific examples of ceria-based solid solutions include ceria doped with one or more dopants (zirconium, lanthanum, yttrium, etc.).
[0014] As the oxide, ceria and ceria-based solid solutions are preferable. Ceria and ceria-based solid solutions are reducible oxides, and can be partially reduced under H2 flow to form oxygen vacancies (oxygen defects) on the surface. Therefore, according to the above configuration, the oxygen vacancies that can be formed on the surface by hydrogen for CO2 hydrogenation used in the reverse water gas shift reaction, or the oxygen vacancies formed on the surface in advance by hydrogen reduction, can improve the adsorption of CO2 and activate CO2. Therefore, according to the above configuration, there is an advantage that the reverse water gas shift reaction can be easily promoted.
[0015] In the present catalytic body, the catalyst contains a main element and a sub-element. The main element is specifically composed of a d-block element. Examples of the d-block element include metal elements such as Co, Fe, Cu, Mo, W, Re, Ru, Rh, Pd, and Pt. These elements can be used alone or in combination of two or more. From the viewpoint of proper adsorption and activation of H2 and proper adsorption and dissociation of CO, the d-block element is preferably Co, Fe, Cu, etc., and more preferably Co.
[0016] The sub-element is at least one of a group 13 element and a group 14 element. Examples of the group 13 element include Al, Ga, In, Tl, and Nh. These elements can be used alone or in combination of two or more. The group 13 element is preferably In, Ga, and more preferably In. Examples of the group 14 element include Si, Ge, Sn, Pb, and Fl. These elements can be used alone or in combination of two or more. The group 14 element is preferably Ge, Sn, and more preferably Ge.
[0017] The above-mentioned oxides, main elements of the catalyst, and sub-elements can be combined in any desired manner.
[0018] In the present catalytic body, the catalyst can be configured to have an oxide containing a main element and an oxide containing a subelement, and / or an oxide containing a main element and a subelement (composite oxide). The present catalytic body according to this configuration can be manufactured, for example, by preparing an aqueous solution containing a desired oxide (an oxide containing a main element and an oxide containing a subelement, or an oxide containing a main element and a subelement) or a precursor thereof so as to obtain a desired loading amount, adding an oxide as a carrier to the aqueous solution and drying it, and then subjecting the resulting dried product to a heat treatment in an oxidizing atmosphere containing oxygen such as the air, and molding, crushing, sizing, etc., as necessary. The present catalytic body according to this configuration may be used after being subjected to a reduction treatment in advance with H2 or the like as necessary, or may be used without being subjected to a reduction treatment in advance. When a reduction treatment is not performed in advance (before a reduction treatment), the above-mentioned desired oxide can be reduced by H2 supplied during the reverse water gas shift reaction, or by a reduction treatment with H2 that may be performed as a pretreatment for the reverse water gas shift reaction.
[0019] In the present catalytic body, the catalyst may have a configuration having an alloy containing a main element and a sub-element. The present catalytic body with this configuration can be manufactured by carrying out a heat treatment in an oxidizing atmosphere in the above-mentioned manufacturing method, followed by a reduction treatment with H2 or the like. The reduction treatment in this case may be carried out before use in the reverse water gas shift reaction, or may be carried out by a reduction treatment with H2 that may be carried out as a pretreatment for the reverse water gas shift reaction. The alloy containing a main element and a sub-element may specifically be a solid solution containing a main element and a sub-element, an intermetallic compound containing a main element and a sub-element, or a state in which both a solid solution containing a main element and a sub-element and an intermetallic compound containing a main element and a sub-element are present. The main form of the alloy containing a main element and a sub-element, either a solid solution containing a main element and a sub-element or an intermetallic compound containing a main element and a sub-element, can be adjusted by the mass ratio of the main element and the sub-element, etc. The intermetallic compound is more likely to be formed as the amount of the sub-element increases. The alloy containing the main element and the sub-element preferably contains an intermetallic compound containing the main element and the sub-element. As will be understood from the experimental examples described later, the formation of the intermetallic compound makes it easier to obtain a high CO selectivity. The oxide used as the support can be prepared, for example, by drying a precipitate obtained by a reverse homogeneous precipitation method or the like, and then subjecting the precipitate to a heat treatment in an oxidizing atmosphere containing oxygen, such as air.
[0020] In the present catalytic body, when the catalyst has a configuration having an alloy containing a main element and a sub-element, the catalytic activity in the reverse water gas shift reaction can be ensured compared to when the catalyst has a configuration having an oxide containing the main element and an oxide containing the sub-element, and / or an oxide containing the main element and the sub-element.
[0021] In the present catalyst, the content of the auxiliary element (which may also be referred to as the amount of the auxiliary element supported, added, or combined) may be preferably 0.2% by mass or more, more preferably 0.3% by mass or more, even more preferably 0.4% by mass or more, and even more preferably 0.5% by mass or more, from the viewpoint of CO selective production ability, etc. Also, the content of the auxiliary element may be preferably 20% by mass or less, more preferably 18% by mass or less, even more preferably 16% by mass or less, even more preferably 14% by mass or less, and even more preferably 12% by mass or less, from the viewpoint of suppressing a decrease in CO2 conversion rate, etc.
[0022] The content of the auxiliary element in the present catalyst body can be calculated by the formula: 100×(mass of the auxiliary element when converted to metal) / (mass of the main element when converted to oxide+mass of the auxiliary element when converted to oxide+mass of the oxide as the support). More specifically, for example, when the oxide as the support is CeO2, the main element is Co, and the auxiliary element is In, the In content can be calculated by the formula: 100×(mass of In metal) / (mass of Co oxide+mass of In oxide+mass of CeO2). Note that, when the oxide as the support is other than CeO2, when the main element is other than Co such as Fe, Cu, or when the auxiliary element is other than In such as Ga, Ge, Sn, the content of the auxiliary element can be calculated in the same manner as above. Note that, the type of oxide to function as the support in the present catalyst body, and the types of the main element and the auxiliary element in the catalyst can be grasped by STEM-EDS analysis. The type of oxide to be used as the support and the amounts of the main and sub-elements in the catalyst can be determined by X-ray fluorescence analysis, high-frequency inductively coupled plasma atomic emission spectrometry, or the like.
[0023] This catalyst has the above-mentioned structure. Therefore, when this catalyst is used in the reverse water gas shift reaction, it can suppress the generation of CH4 and improve the CO selectivity. Although the detailed mechanism is not clear, CO2 adsorbed to an oxide capable of adsorbing carbon dioxide gas on its surface becomes an intermediate (formate), but since the supply of H is partially inhibited by the auxiliary element, it is considered that, although the CO2 conversion rate is lower than when no auxiliary element is used, that is, when the catalyst is composed of the main element alone, the generation of CH4 is suppressed and the CO selectivity is improved.
[0024] Furthermore, with this catalyst, in a CO (carbon monoxide) production method that includes a reverse water-gas shift reaction process in which a raw material gas containing CO2 (carbon dioxide) and H2 (hydrogen) is contacted with this catalyst to obtain a product gas containing CO (carbon monoxide), it is possible to suppress the production of CH4 and improve CO selectivity.
[0025] The above-mentioned configurations can be arbitrarily combined as necessary to obtain the above-mentioned functions and effects. EXAMPLES
[0026] <Experimental Example> The present catalyst will now be described in more detail with reference to experimental examples.
[0027] (Experimental Example 1) The purpose of this experimental example is to measure the catalytic activity of each catalyst in which Co, Fe, or Cu is supported on CeO2, an oxide capable of adsorbing carbon dioxide gas on its surface, and to examine the influence of the catalytic metal.
[0028] CeO2 was prepared by the reverse homogeneous precipitation method. Specifically, 27.1415 g of Ce(NO3)3·6H2O was first dissolved in 100 mL of ultrapure water by stirring with a magnetic stirrer. This aqueous solution was then added to 250 mL of 28% ammonia water while stirring, and stirred for 1 hour. After 1 hour, the stirring was stopped and the mixture was left to stand for 20 minutes to separate the supernatant and precipitate. The supernatant liquid resulting from the separation was discarded, and 350 mL of ultrapure water was added to the remaining precipitate layer, stirred for 30 minutes, and then left to stand for 20 minutes after stirring. The above-mentioned operation of discarding the supernatant and leaving it to stand was repeated four times in total to wash the precipitate. The precipitate was then separated into liquid components by suction filtration. The obtained precipitate was dried overnight in a dryer maintained at 80°C. The solid obtained after drying was crushed using a mortar and pestle, and subjected to heat treatment. The heat treatment was first performed in a box-type electric furnace at 300°C for 3 hours in an air atmosphere, then in a horizontal tubular furnace at 550°C for 3 hours under air flow, and finally in a box-type electric furnace at 700°C for 5 hours in an air atmosphere. Through the above steps, CeO2 to be used as a support was obtained.
[0029] Co(20) / CeO2 was prepared by impregnation, in which 20% by mass of Co was supported on CeO2. Specifically, first, the metal precursor Co(NO3)2·6H2O was dissolved in 150 mL of ultrapure water by stirring with a magnetic stirrer. Then, after confirming that it had dissolved, the solution was stirred for an additional hour to homogenize the aqueous solution. After one hour had passed, 1.5 g of CeO2 was added and stirred overnight. Next, the water was evaporated under reduced pressure of 0.01 MPa using a rotary evaporator set at a water bath temperature of 70°C and a rotation speed of 10, and then dried overnight in a dryer maintained at 80°C. The solid obtained after drying was then crushed using a mortar and pestle and heated in a horizontal tubular furnace at 400°C for 5 hours under air circulation.
[0030] Fe(20) / CeO2 was prepared by loading 20 mass% Fe on CeO2 in the same manner as above, except that the metal precursor was changed to Fe(NO3)3·9H2O. Cu(20) / CeO2 was prepared by loading 20 mass% Cu on CeO2 in the same manner as above, except that the metal precursor was changed to Cu(NO3)2·3H2O. The catalyst prepared in this manner was first formed into a disk shape by uniaxial molding, and then crushed to a particle size of 250-500 μm.
[0031] The catalytic activity of each catalyst, Co(20) / CeO2, Fe(20) / CeO2, and Cu(20) / CeO2, was measured by reverse water-gas shift reaction experiments. Specifically, a fixed-bed flow reactor was used for the catalytic activity measurement by reverse water-gas shift reaction experiments. A ribbon heater was used to maintain 50°C from the reaction tube outlet to the water trap to prevent condensation of the generated water. An online GC-TCD (GL Sciences "GC3200") was used to analyze the products. A metal reaction tube was used. The catalyst layer was fixed with quartz wool, and a thermocouple was installed to measure the temperature of the catalyst layer. The amount of catalyst was 150 mg.
[0032] In the reverse water gas shift reaction experiment, a reduction treatment was first performed at 500°C for 1 hour as a pretreatment under the flow of H2 (50cc / min). The heating rate up to 500°C was 10°C / min. After the reduction treatment, Ar (50cc / min) was circulated for 30 minutes at 500°C to purge the reaction tube. After Ar purging, the temperature was lowered to 150°C, which is the reaction initiation temperature, while continuing the flow of Ar, and the reaction was started by supplying H2 (20cc / min), CO2 (5cc / min), and N2 (2cc / min). Here, N2 was introduced as an internal standard. The reaction pressure was atmospheric pressure. The reaction temperature was in the range of 150°C to 450°C, and analysis was performed every 50°C. Analysis was performed five times at each temperature, and the CO2 conversion rate (CO2conversion) (%) and CO selectivity (COselectivity) (%) were calculated based on the average values of the results obtained. In this experiment, the volume changes before and after the reactor, so the carbon balance of CO2, CO, and CH4 was used to correct for this. The results are shown in Figures 1 and 2.
[0033] According to Figures 1 and 2, the monometallic catalyst Co had a higher CO2 conversion rate but a lower CO selectivity than the monometallic catalysts Fe and Cu. From these results, it can be seen that if the CO selectivity of Co / CeO2, in which the monometallic catalyst Co is supported on CeO2, can be improved, a catalyst body with both high CO2 conversion rate and CO selectivity can be obtained. Therefore, in the next Experimental Example 2, we decided to examine the improvement of the CO selectivity of Co / CeO2.
[0034] (Experimental Example 2) The purpose of this experimental example is to confirm the effect of adding a Group 13 element or Group 14 element of the p-block as an auxiliary element in order to improve the CO selectivity of Co / CeO2 produced in Experimental Example 1. In this experimental example, In was used as the Group 13 element, and Ge or Sn was used as the Group 14 element.
[0035] Co(20) / CeO2 was prepared in the same manner as in Experimental Example 1.
[0036] In addition, a catalyst in which Ge was added to Co(20) / CeO2 was prepared by the co-impregnation method. Specifically, Co(NO3)2·6H2O and GeO2 were dissolved in ultrapure water to obtain a precursor aqueous solution. Except for using this precursor aqueous solution, the same procedure as in Experimental Example 1 was used to prepare Co(20)-Ge(2) / CeO2, in which 20 mass% Co and 2 mass% Ge were supported on CeO2.
[0037] In addition, a catalyst in which Sn was added to Co(20) / CeO2 was prepared by the co-impregnation method. Specifically, Co(NO3)2·6H2O and SnCl4·5H2O were dissolved in ultrapure water to obtain a precursor aqueous solution. Except for using this precursor aqueous solution, the same procedure as in Experimental Example 1 was used to prepare Co(20)-Sn(2) / CeO2, in which 20 mass% Co and 2 mass% Sn were supported on CeO2.
[0038] In addition, a catalyst in which In was added to Co(20) / CeO2 was prepared by the co-impregnation method. Specifically, Co(NO3)2·6H2O and In(NO3)3·3H2O were dissolved in ultrapure water to obtain a precursor aqueous solution. Except for using this precursor aqueous solution, the same procedure as in Experimental Example 1 was used to prepare Co(20)-In(2) / CeO2, which supports 20 mass% Co and 2 mass% In on CeO2.
[0039] For each of the catalysts Co(20) / CeO2, Co(20)-Ge(2) / CeO2, Co(20)-Sn(2) / CeO2, and Co(20)-In(2) / CeO2, catalytic activity was measured by reverse water-gas shift reaction in the same manner as in Experimental Example 1. The results are shown in Figures 3 and 4.
[0040] 3 and 4, the CO2 conversion rate satisfies the magnitude relationship of the catalyst body having a monometallic catalyst Co >> the catalyst body having a catalyst containing Co and Ge > the catalyst body having a catalyst containing Co and Sn > the catalyst body having a catalyst containing Co and In. On the other hand, the CO selectivity is significantly improved in all of the catalyst bodies having a catalyst containing Co and Ge, the catalyst body having a catalyst containing Co and Sn, and the catalyst body having a catalyst containing Co and In, compared with the catalyst body having a monometallic catalyst Co. Therefore, in the next Experimental Example 3, the effect of the amount of Ge supported (content, amount added) was examined.
[0041] In this experimental example, X-ray diffraction measurements (XRD) were performed in an air atmosphere for each catalyst body before (immediately after calcination) and after reduction treatment in the reverse water gas shift reaction experiment, and the crystal structure of each catalyst body was analyzed. In addition, to investigate the effect of adding Ge, Sn, and In to the catalyst body having a monometallic Co catalyst on the reduction behavior, a temperature-programmed reduction measurement (H2-TPR) was performed under a hydrogen flow. These are explained below.
[0042] The X-ray diffraction measurement (XRD) was carried out as follows. Specifically, first, the catalyst body sample was thoroughly ground in an agate mortar before the measurement. Then, it was filled into a non-reflective sample holder made of Si, and the diffraction pattern was measured using an X-ray diffractometer (Rigaku's "Smart-Lab"). At this time, the tube voltage was 40 kV and the tube current was 30 mA. All catalyst body samples were measured under the conditions of 2θ=10-80°, a scanning speed of 20 degrees / min, and a sampling rate of 0.02 degrees. Furthermore, the samples before the reduction treatment (immediately after calcination) were measured in the range of 2θ=35.5-38.5°, and the samples after the reduction treatment were measured in the range of 2θ=43-46°, under the conditions of a scanning speed of 1 degree / min and a sampling rate of 0.0052 degrees. The results are shown in Figures 5 and 7.
[0043] Temperature-programmed reduction measurements (H2-TPR) were performed as follows. Specifically, 0.1 g of catalyst sample (before reduction treatment) was first placed in a quartz tube reactor and attached to a fully automatic temperature-programmed desorption analyzer (Microtrack-Bel's "BELCAT II"). 100% H2 was then passed through at 50 cc / min, and the temperature was raised from 35°C to 1000°C in this state (heating rate 10°C / min). The desorbed H2O was observed with a mass spectrometer (MS). The results are shown in Figure 6.
[0044] As shown in Figure 5, in each catalyst body before reduction treatment (immediately after calcination) to which Ge, Sn, and In were added, when Ge and Sn were added, a peak growth of Co3O4 was observed, and when In was added, a peak shift was observed. This indicates that some In formed a complex oxide with Co. In addition, in each catalyst body before reduction treatment (immediately after calcination) to which Ge, Sn, and In were added, basically only diffraction peaks derived from the oxides of Ce and Co were observed. This indicates that the amount of Ge, Sn, and In supported was small at 2 mass%, and therefore they were distributed in the catalyst with small crystal sizes that could not be detected by XRD.
[0045] As shown in Fig. 6, the peak shift to the high temperature side was observed in each catalyst body before reduction treatment with Ge, Sn, and In added, by hydrogen reduction by temperature-programmed reduction measurement (H2-TPR). The above peak shift amount was larger in the order of higher CO selectivity (In>Sn>Ge). Here, in the reduction of metal oxides, hydrogen molecules dissociate on the surface to become active atomic hydrogen, and this atomic hydrogen is thought to extract oxygen from the metal oxide, thereby progressing the reduction. In other words, the shift of the reduction peak to the high temperature side indicates that Co oxide (Co3O4) is difficult to reduce. This is thought to be because hydrogen atoms are difficult to dissociate on Ge, Sn, In, or their oxides, which inhibits the generation of atomic hydrogen necessary for the reduction of Co oxide. The elements for which the peak shift to the high temperature side was observed show that hydrogen dissociation is difficult to occur, that is, the supply of H is inhibited, which coincides with the order of CO selectivity.
[0046] As shown in Figure 7, in each catalyst after reduction treatment with Ge, Sn, or In added, diffraction peaks due to CeO2 and only diffraction peaks due to Co metal were observed. When Ge or In was added, the diffraction peaks due to Co metal shifted to lower angles. When Sn was added, no shift of the Co peak to lower angles was observed. From these results, it is inferred that the additives affect the crystal structure of Co.
[0047] The crystal grain size of Co3O4 before the reduction treatment was 31 nm for Co(20) / CeO2, 50 nm for Co(20)-Ge(2) / CeO2, 54 nm for Co(20)-Sn(2) / CeO2, and 21 nm for Co(20)-In(2) / CeO2. The crystal grain size of Co after the reduction treatment was 26 nm for Co(20) / CeO2, 20 nm for Co(20)-Ge(2) / CeO2, 31 nm for Co(20)-Sn(2) / CeO2, and 27 nm for Co(20)-In(2) / CeO2. The above crystal grain size is a value calculated by Scherrer's formula using the half-width of the diffraction peak derived from the (111) plane of metal Co, which appears near 44 ° in the X-ray diffraction pattern (the same applies below, so the explanation is omitted).
[0048] (Experimental Example 3) The purpose of this experimental example is to examine the effect of the amount of Ge supported in a catalyst body having CeO2 and a catalyst containing Co as a main element and Ge as a sub-element.
[0049] The following catalysts with different Ge loading amounts were prepared in the same manner as in Experimental Example 2. The Ge loading amount was adjusted by adjusting the masses of Co(NO3)2·6H2O and GeO2 dissolved in ultrapure water to achieve a predetermined theoretical loading amount. GeO2 is soluble in water, but becomes difficult to dissolve at high masses, so it was dissolved by heating within the range of 30℃ to 50℃. Co(20)-Ge(0.2) / CeO2, which is CeO2 carrying 20 mass% Co and 0.2 mass% Ge. Co(20)-Ge(0.5) / CeO2, which is a CeO2 supported with 20 mass% Co and 0.5 mass% Ge. Co(20)-Ge(1) / CeO2, which is CeO2 loaded with 20% Co and 1% Ge by mass. Co(20)-Ge(2) / CeO2, which is CeO2 carrying 20% Co and 2% Ge by mass. Co(20)-Ge(4) / CeO2, which is CeO2 carrying 20% Co and 4% Ge by mass. Co(20)-Ge(10) / CeO2, which is CeO2 carrying 20 mass% Co and 10 mass% Ge. Co(20)-Ge(20) / CeO2, which is CeO2 carrying 20 mass% Co and 20 mass% Ge.
[0050] Co(20) / CeO2 was prepared in the same manner as in Experimental Example 1. Ge(20) / CeO2 in which 20 mass% of Ge was supported on CeO2 was prepared in the same manner as in Experimental Example 1, except that the metal precursor was changed to GeO2.
[0051] For each of the above catalyst bodies, catalytic activity was measured by a reverse water gas shift reaction experiment in the same manner as in Experimental Example 1. The results are shown in Figs. 8 to 10.
[0052] As shown in Figures 8 to 10, the CO2 conversion rate decreased with an increase in the Ge loading. When the Ge loading was in the range of 1 to 10 mass%, the CO2 conversion rate hardly changed. The CO selectivity improved with an increase in the Ge loading. In particular, when the Ge loading was 0.5 mass% or more, and especially when the Ge loading was 1 mass% or more, the CO selectivity at high temperatures improved significantly.
[0053] In this experimental example, similar to Experimental Example 2, X-ray diffraction measurements (XRD) were performed in the air for each catalyst body before (immediately after calcination) and after the reduction treatment in the reverse water gas shift reaction experiment, and the crystal structure of each catalyst body was analyzed. Furthermore, in this experimental example, X-ray diffraction measurements (XRD) were performed in the air for each catalyst body after the reverse water gas shift reaction experiment, and the crystal structure of each catalyst body was also analyzed. Furthermore, in this experimental example, similar to Experimental Example 2, in order to investigate the effect of the amount of Ge added to the catalyst body having the monometallic catalyst Co on the reduction behavior, a temperature-programmed reduction measurement (H2-TPR) was performed under hydrogen flow. These results are shown in Figures 11 to 14.
[0054] As shown in FIG. 11, in each Co-Ge / CeO2 catalyst body before reduction treatment (immediately after calcination) with different Ge loading amounts, Co3O4 peak growth was observed in the Ge loading amount range of 0 mass% to 20 mass%, and no peak shift was observed. In addition, a GeO2 peak appeared in the Ge loading amount range of 4 mass% to 20 mass%. In addition, in each Co-Ge / CeO2 catalyst body before reduction treatment (immediately after calcination), basically only diffraction peaks derived from the oxides of Ce, Co, and Ge were observed. From these results, it is considered that Co and Ge exist as their respective oxides in each Co-Ge / CeO2 catalyst body before reduction treatment (immediately after calcination).
[0055] In addition, as shown in Fig. 12, in each Co-Ge / CeO2 catalyst body before reduction treatment (immediately after calcination) with different Ge loading amounts, the reduction peak of Co3O4 shifted to the high temperature side by hydrogen reduction by temperature-programmed reduction measurement (H2-TPR). Specifically, when the Ge loading amount was in the range of 0.2 mass% to 2 mass%, the reduction peak of Co3O4 shifted to the high temperature side, and when the Ge loading amount was in the range of 2 mass% to 20 mass%, no further peak shift of Co3O4 was observed. In addition, when the Ge loading amount was in the range of 4 mass% to 20 mass%, the reduction peak of GeO2 appeared and gradually shifted to the high temperature side. From these results, it is considered that when the Ge loading is in the range of 0.2 to 4 mass%, GeO2 is mainly distributed near the surface of the Co3O4 particles, inhibiting hydrogen dissociation and its supply to the Co3O4 surface, and that when the Ge loading is in the range of 4 to 20 mass%, GeO2 is distributed in places other than the surface of the Co3O4 particles.
[0056] In addition, as shown in FIG. 13, in each of the Co-Ge / CeO2 catalyst bodies after reduction treatment with different Ge loading amounts, in the range of Ge loading amounts from 0 mass% to 4 mass%, only diffraction peaks derived from Co metal were observed in addition to diffraction peaks derived from CeO2. However, when the Ge loading amount is 4 mass%, the diffraction peaks derived from Co metal shift to the low angle side, so it is considered that the main element Co and the sub-element Ge form an alloy. In addition, from the analysis results of STEM-EDS described later, it is considered that even when the Ge loading amount is 0.5 mass%, most of the Ge forms an alloy with Co. In addition, in the range of Ge loading amounts from 10 mass% to 20 mass%, diffraction peaks derived from Ge and Co-Ge alloys (specifically, intermetallic compounds) were observed.
[0057] In addition, as shown in Fig. 14, no significant changes were observed in the Co-Ge / CeO2 catalysts with different Ge loading amounts after the reverse water gas shift reaction experiment compared to after the reduction treatment. This result confirmed that this catalyst can be used repeatedly in the reverse water gas shift reaction.
[0058] The crystal grain sizes of Co3O4 before the reduction treatment were 31 nm for Co(20) / CeO2, 35 nm for Co(20)-Ge(0.2) / CeO2, 50 nm for Co(20)-Ge(2) / CeO2, 45 nm for Co(20)-Ge(4) / CeO2, 48 nm for Co(20)-Ge(10) / CeO2, and 62 nm for Co(20)-Ge(20) / CeO2. In addition, the crystal grain size of Co after the reduction treatment was 26 nm for Co(20) / CeO2, 24 nm for Co(20)-Ge(0.2) / CeO2, 20 nm for Co(20)-Ge(2) / CeO2, 19 nm for Co(20)-Ge(4) / CeO2, 24 nm for Co(20)-Ge(10) / CeO2, and 80 nm for Co(20)-Ge(20) / CeO2.
[0059] (Experimental Example 4) The purpose of this experimental example is to investigate the microstructure of the catalyst body having CeO2 and a catalyst containing Co as a main element and Ge as a sub-element by STEM-EDS analysis, which was prepared in Experimental Example 3. In this experimental example, the catalyst bodies used for STEM-EDS analysis were the Co(20) / CeO2 catalyst body after reduction treatment, the Co(20)-Ge(20) / CeO2 catalyst body before reduction treatment (immediately after calcination), and the Co(20)-Ge(20) / CeO2 catalyst body after reduction treatment, which were prepared in Experimental Example 3. The results are shown in Figures 15 to 19.
[0060] FIG. 15 shows the results of STEM-EDS analysis of the Co(20) / CeO2 catalyst after reduction. FIG. 15 shows that the Co(20) / CeO2 catalyst after reduction is in a state where aggregates of Co on the scale of several hundreds of nm and CeO2 particles are mixed. FIG. 16 shows the results of STEM-EDS analysis of the Co(20) / CeO2 catalyst after reduction (at a higher magnification than FIG. 15). FIG. 16 shows that the diameter of the CeO2 particles is about several tens of nm, and the particle size is relatively uniform. It also shows that some Co is supported on the Co in a fine state of about <10 nm.
[0061] Figure 17 shows the results of STEM-EDS analysis of the Co(20)-Ge(20) / CeO2 catalyst after reduction. Figure 17 shows that the Co(20)-Ge(20) / CeO2 catalyst after reduction is in a state where several hundred nm-scale Co-Ge alloy aggregates (as can be seen from the overlap of the Co K and Ge K photographs) are mixed with CeO2 particles. In addition, some of the Ge is also dispersed on the Ce, but most of it is in the same position as the Co, which shows that Co and Ge easily form an alloy.
[0062] Figure 18 shows the results of STEM-EDS analysis (at a higher magnification than Figure 18) of the Co(20)-Ge(20) / CeO2 catalyst after reduction treatment. Figure 18 shows that Ge and Co are present in the same position, but the concentrations (color intensities of each element map) vary, and even if Co and Ge form an alloy, the concentration is not uniform.
[0063] Figure 19 shows the results of STEM-EDS analysis of the Co(20)-Ge(20) / CeO2 catalyst before reduction (immediately after calcination) and after the reverse water gas shift reaction. Figure 19 shows that Co and Ge are present in the same position, as in the results after reduction. This result shows that an alloy of Co and Ge is formed in the hydrogen reduction atmosphere of the reverse water gas shift reaction, even without a separate reduction treatment.
[0064] (Experimental Example 5) The purpose of this experimental example is to compare the CO conversion rate and CO selectivity of the following catalysts: Fe(20) / CeO2 (20 mass% Co supported on CeO2), Cu(20) / CeO2 (20 mass% Cu supported on CeO2), and Co(20)-Ge(10) / CeO2 (20 mass% Co and 10 mass% Ge supported on CeO2).
[0065] Fe(20) / CeO2 and Cu(20) / CeO2 were prepared in the same manner as in Experimental Example 1. Co(20)-Ge(10) / CeO2 was prepared in the same manner as in Experimental Example 3.
[0066] For each of the above catalyst bodies, catalytic activity was measured by a reverse water gas shift reaction experiment in the same manner as in Experimental Example 1. The results are shown in Figs. 20 and 21.
[0067] 20 and 21 show that the catalyst body having a catalyst containing Co as the main element and Ge as the sub-element can suppress the production of CH4, and has a CO selective production ability comparable to that of the catalyst body having monometallic catalysts such as Fe and Cu.
[0068] (Experimental Example 6) The purpose of this experimental example is to examine the effect of the amount of In supported in a catalyst body having CeO2 and a catalyst containing Co as a main element and In as a sub-element.
[0069] The following catalysts with different amounts of In were prepared in the same manner as in Experimental Example 2. The amount of In supported was adjusted by adjusting the masses of Co(NO3)2·6H2O and In(NO3)3·3H2O dissolved in ultrapure water to obtain a predetermined theoretical amount. Co(20)-In(0.2) / CeO2, which is a CeO2 supported with 20 mass% Co and 0.2 mass% In. Co(20)-In(4) / CeO2, which is a CeO2 supported with 20 mass% Co and 4 mass% In. Co(20)-In(10) / CeO2, which is a CeO2 supported with 20 mass% Co and 10 mass% In. Co(20)-In(20) / CeO2, which is CeO2 carrying 20 mass% Co and 20 mass% In.
[0070] In addition, Co(20) / CeO2 was prepared in the same manner as in Experimental Example 1.
[0071] For each of the above catalyst bodies, catalytic activity was measured by a reverse water gas shift reaction experiment in the same manner as in Experimental Example 1. The results are shown in Figs.
[0072] As shown in Figures 22 and 23, the CO2 conversion rate decreased with an increase in the amount of In supported. The CO selectivity improved with an increase in the amount of In supported. In particular, when the amount of In supported was 2 mass% or more, the CO selectivity improved significantly.
[0073] In this example, similar to Example 2, X-ray diffraction measurements (XRD) were performed in an air atmosphere for each catalyst body before (immediately after calcination) and after reduction treatment in the reverse water gas shift reaction experiment, and the crystal structure of each catalyst body was analyzed. In this example, similar to Example 2, temperature-programmed reduction measurements (H2-TPR) were performed under hydrogen flow to investigate the effect of the amount of In added to the catalyst body having the monometallic Co catalyst on the reduction behavior. These results are shown in Figures 24 to 26.
[0074] As shown in FIG. 24, in each Co-In / CeO2 catalyst body before reduction treatment (immediately after calcination) with different In loading amounts, the Co3O4 peak shifted to the lower angle side when the In loading amount was in the range of 0 mass% to 20 mass%. In addition, when the In loading amount was 10 mass% and 20 mass%, an In2O3 peak appeared. In each Co-In / CeO2 catalyst body before reduction treatment (immediately after calcination), basically only diffraction peaks derived from the oxides of Ce, Co, and In were observed. From these results, it is considered that in each Co-In / CeO2 catalyst body before reduction treatment (immediately after calcination), oxides of Co and In, or composite oxides containing Co and In, exist.
[0075] In addition, as shown in FIG. 25, in each of the Co-In / CeO2 catalyst bodies before reduction treatment (immediately after calcination) with different In loading amounts, the reduction peak of Co3O4 was shifted to the high temperature side by hydrogen reduction by temperature-programmed reduction measurement (H2-TPR). Specifically, when the In loading amount was in the range of 0.2 mass% to 2 mass%, the reduction peak of Co3O4 was shifted to the high temperature side, and when the In loading amount was in the range of 2 mass% to 20 mass%, no further peak shift of Co3O4 was observed. In addition, when the In loading amount was 10 mass% or 20 mass%, the reduction peak of In2O3 appeared and gradually shifted to the high temperature side. From these results, it is considered that when the In loading amount is in the range of 2 mass% or more, Co and In form a complex oxide, and a site of Co that is difficult to reduce is formed.
[0076] As shown in FIG. 26, in each of the Co-In / CeO2 catalysts after the reduction treatment with different amounts of In loaded, in addition to the diffraction peaks due to CeO2, only diffraction peaks due to Co metal and diffraction peaks due to CoIn2 were observed. In addition, when the amount of In loaded was in the range of 0.2 mass% to 2 mass%, the Co peak shifted to the low angle side. In addition, when the amount of In loaded was in the range of 2 mass% to 20 mass%, the shift amount increased with increasing amount of In loaded. In addition, when the amount of In loaded was 10 mass% and 20 mass%, the reduction peak of CoIn2 appeared. From these results, it is considered that Co and In form an alloy by the reduction treatment, and as the amount of In loaded increases, an alloy site rich in In is formed in the crystal structure.
[0077] The crystal grain sizes of Co3O4 before the reduction treatment were 31 nm for Co(20) / CeO2, 45 nm for Co(20)-In(0.2) / CeO2, 21 nm for Co(20)-In(2) / CeO2, 22 nm for Co(20)-In(4) / CeO2, 19 nm for Co(20)-In(10) / CeO2, and 19 nm for Co(20)-In(20) / CeO2. In addition, the crystal grain size of Co after the reduction treatment was 26 nm for Co(20) / CeO2, 29 nm for Co(20)-In(0.2) / CeO2, 27 nm for Co(20)-In(2) / CeO2, 28 nm for Co(20)-In(4) / CeO2, 34 nm for Co(20)-In(10) / CeO2, and 56 nm for Co(20)-In(20) / CeO2.
[0078] (Experimental Example 7) The purpose of this experimental example is to compare the CO yield when the present catalyst is used in a reverse water gas shift reaction experiment with the CO yield of a comparative catalyst.
[0079] In this experimental example, the following catalysts prepared in the above experimental examples were used as the present catalyst and the comparative catalyst, and the CO yield at each temperature was obtained. The results are shown in Figures 27 to 30. The CO yield can be calculated from the CO2 conversion rate x CO selectivity. Figure 27 corresponds to Figures 1 and 2. Figure 28 corresponds to Figures 3 and 4. Figure 29 corresponds to Figures 8 and 9. Figure 30 corresponds to Figure 20. <This catalyst body> Co(20)-Ge(0.2) / CeO2 Co(20)-Ge(2) / CeO2 Co(20)-Ge(4) / CeO2 Co(20)-Ge(10) / CeO2 Co(20)-Ge(20) / CeO2 Co(20)-Sn(2) / CeO2 Co(20)-In(2) / CeO2 <Catalyst for comparison> ·Co(20) / CeO2 Fe(20) / CeO2 Cu(20) / CeO2
[0080] 27 to 30 show that the present catalyst body having CeO2 and a catalyst containing Co as a main element and Ge, Sn, or In as a sub-element can significantly improve the CO yield compared to the comparative catalyst body having the monometallic catalyst Co.
[0081] Although the examples of the present invention have been described in detail above, the present invention is not limited to the above-mentioned embodiments and experimental examples, and various modifications are possible within the scope that does not depart from the spirit of the present invention.
[0082] The features of the present invention are as follows. [1] The catalyst has an oxide capable of adsorbing carbon dioxide gas on its surface, and a catalyst; The catalyst comprises a main element consisting of a d-block element and a sub-element consisting of at least one of a Group 13 element and a Group 14 element, Catalyst for reverse water gas shift reaction. [2] The catalyst is an alloy comprising the main element and the sub-element; The oxide includes an oxide containing the main element and an oxide containing the sub-element, and / or an oxide containing the main element and the sub-element. The catalyst for reverse water gas shift reaction according to [1]. [3] The main element is Co, Fe or Cu; The catalyst for reverse water gas shift reaction according to [1] or [2]. [4] the group 13 element is In or Ga, The group 14 element is Ge or Sn; The catalyst for reverse water gas shift reaction according to any one of [1] to [3]. [5] The oxide is ceria or a ceria-based solid solution; The catalyst for reverse water gas shift reaction according to any one of [1] to [4]. [6] The content of the auxiliary element is 0.2% by mass or more. The catalyst for reverse water gas shift reaction according to any one of [1] to [5].
Claims
1. The catalyst has an oxide capable of adsorbing carbon dioxide gas on its surface, and a catalyst; The catalyst comprises a main element consisting of a d-block element and a sub-element consisting of at least one of a Group 13 element and a Group 14 element. Catalyst for reverse water gas shift reaction.
2. The catalyst is an alloy comprising the main element and the sub-element; The oxide includes an oxide containing the main element and an oxide containing the sub-element, and / or an oxide containing the main element and the sub-element. The reverse water gas shift reaction catalyst according to claim 1 .
3. The main element is Co, Fe or Cu; The catalyst for reverse water gas shift reaction according to claim 1 or 2.
4. the group 13 element is In or Ga, The group 14 element is Ge or Sn; The catalyst for reverse water gas shift reaction according to claim 1 or 2.
5. The oxide is ceria or a ceria-based solid solution; The catalyst for reverse water gas shift reaction according to claim 1 or 2.
6. The content of the auxiliary element is 0.2 mass% or more. The catalyst for reverse water gas shift reaction according to claim 1 or 2.